Improvement of a disk diffusion method for antibiotic susceptibility testing of anaerobic bacteria. French recommendations revisited for 2020. (August 2020) - Dubreuil, L.; ,; Jehl, F.; Cattoen, C.; Bonnet, R.; Bru, J.P.; Caron, F.; Cattoir, Vincent; Courvalin, Patrice; Jarlier, Vincent; Lina, Gérard; Merens, Audrey; et al.
Abstract: The disk diffusion test is very popular but for anaerobes the main pitfalls arise from the significant variation of diameters for an individual MIC and the weak correlation observed between the MIC's values and diameters zone that generates many major and very major errors. Aims of the study: without any change in the methodology and revisiting only new diameter breakpoints, we try to improve the previous French recommendations and therefore decrease number of errors by introducing recent EUCAST concepts such as ECOFF and ATU Zone. Method: MIC determination by agar dilution was done on 100 anaerobes against 6 antibiotics. Clinical categorization was based on EUCAST Breakpoints. Disk-diffusion method was realized on the same Brucella blood agar incubated in an anaerobic chamber. 550 categorizations by both methods could be done as amoxicillin was not tested on the 50 B. fragilis group. As anaerobic infections are severe and treated by antibiotics at higher dosage, we focus on resistance breakpoint to avoid mainly very major errors (VME). Distribution of inhibition zones for each MIC allow us to fix the zone diameter breakpoints. These results were matched to a large data on distribution of zone diameters for each antibiotic collected from two French hospitals from 1990 to 2005. As example for metronidazole and the B. fragilis group, we calculated the cut-off diameter (15 mm) from a wild type population, at a time when there was no resistance to this antibiotic and observed that it was identical to the diameter breakpoint for susceptibility. Results: For an individual value of MIC, the distribution of diameters is wider for anaerobes especially for clindamycin and metronidazole. Using a 15 mm breakpoint for these two antibiotics limits dramatically the number of very major errors but slowly increases the number of major errors that could be overcome by MIC determination if inhibition zone is less than 15 mm. ATU zones (Area of technical uncertainty) were introduced for amoxicillin-clavulanate (17–20 mm), piperacillin-tazobactam (17–20 mm), imipenem (18–23 mm). Categorization inside the ATU requires MIC determination. Finally, out of 550 determinations, VME were observed in 1.45% of cases, an acceptable rate. Conclusion: in combination with introduction of ATU zones disk diffusion method allows to detect resistant strains with little MIC determinations and very major errors. Highlights: Disk diffusion method allows detection of antibiotic resistance. ATU zones are needed for some antibiotics. Number of very major errors decrease when diameters results are combined with ATU zone and expert rules. MIC determination may be required in some instances when interpretation is not possible by the diffusion method.